2017
DOI: 10.1016/j.econlet.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Distance, globalization, and international trade

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 24 publications
4
59
0
1
Order By: Relevance
“…The standard gravity equation in equation (1) can be improved by applying it to panel data and by including intranational trade flows, , along with international trade flows, , as in Yotov (2012) and Borchert and Yotov (2017).11 These changes produce the following gravity specification:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard gravity equation in equation (1) can be improved by applying it to panel data and by including intranational trade flows, , along with international trade flows, , as in Yotov (2012) and Borchert and Yotov (2017).11 These changes produce the following gravity specification:…”
Section: Methodsmentioning
confidence: 99%
“…and any home biases in consumption; and is the vector of year dummies that capture the year fixed effects. We follow Yotov (2012) and Borchert and Yotov (2017) As an alternative specification, we allow the origin-country-specific effects and the destination-country-specific effects in equation (2) to vary over time by estimating the following equation:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially after globalization, international trade has developed very much. As a result, the economies of the country became affected by the exchange rate [39,40]. Some countries import their energy needs from abroad because they do not have enough energy sources [41][42][43][44].…”
Section: Literature Review On Gasoline Demandmentioning
confidence: 99%
“…Research conducted by Borchert and Yotov (2017) showed that globalization can affect manufacturing trade in 1986-2006 period and on average the impact has decreased by 10% due to the impact of relations and regional trade agreements that increase over time. It was also known that globalization benefits most in middle-income countries.…”
Section: Introductionmentioning
confidence: 99%